2021
DOI: 10.3390/cimb43020039
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study Showing the Impact of Genetic and Dietary Factors on GC–MS-Based Plasma Metabolome of Patients with and without PROX1-Genetic Predisposition to T2DM up to 5 Years Prior to Prediabetes Appearance

Abstract: Risk factors for type 2 diabetes mellitus (T2DM) consist of a combination of an unhealthy, imbalanced diet and genetic factors that may interact with each other. Single nucleotide polymorphism (SNP) in the prospero homeobox 1 (PROX1) gene is a strong genetic susceptibility factor for this metabolic disorder and impaired β-cell function. As the role of this gene in T2DM development remains unclear, novel approaches are needed to advance the understanding of the mechanisms of T2DM development. Therefore, in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 79 publications
1
10
0
Order By: Relevance
“…Extraction of serum metabolites was performed as described previously (Mojsak et al, 2021). The derivatization procedure was carried out in two steps.…”
Section: Gc-ms-based Metabolomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extraction of serum metabolites was performed as described previously (Mojsak et al, 2021). The derivatization procedure was carried out in two steps.…”
Section: Gc-ms-based Metabolomicsmentioning
confidence: 99%
“…Recent findings have highlighted metabolomics as a prime candidate for evaluating potential markers for GDM (Mao et al, 2017) because of its capacity to detect early deregulations and disruptions in metabolism associated with different diseases (Mojsak et al, 2021). Therefore, it can be used as a potential tool to determine a metabolite or a set of metabolites allowing diagnosis or prediction of GDM (Sakurai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide prevalence of type 2 diabetes mellitus (T2DM) has risen over the past two decades (Sobczak et al, 2019) and currently, this metabolic disease is a serious public health problem (Fikri et al, 2020). There is an increasing evidence that alterations in gut microbiota (GM) (Lin et al, 2017;Moon et al, 2018;Chen et al, 2019), apart from genetic (Mojsak et al, 2021) and life style factors (Ericson et al, 2018), are important for the development of metabolic diseases. Changes in the gut microbiome composition lead to an imbalanced gastrointestinal habitat which promotes abnormal production of metabolites, inflammatory status, glucose metabolism alteration and even insulin resistance (IR) (Tanase et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the gut microbiome composition lead to an imbalanced gastrointestinal habitat which promotes abnormal production of metabolites, inflammatory status, glucose metabolism alteration and even insulin resistance (IR) (Tanase et al, 2020). Particularly, various microbiota-dependent metabolites (MDMs) (Han et al, 2021), such as short-chain fatty acids, branched-chain fatty acids, amino acids (AAs), branched-chain amino acids (BCAAs), bile acids, tryptophanderived metabolites, and others (Mojsak et al, 2022;Zhou et al, 2022) have been reported to be closely associated with IR (Menni et al, 2022), prediabetes (Dorcely et al, 2017;Gar et al, 2018) and T2DM (Sobczak et al, 2019;Fikri et al, 2020;Gu et al, 2020;Mojsak et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation